Comparing the effects of dextrose prolotherapy and extracorporeal shockwave therapy on dynamic balance in knee osteoarthritis patients - Fahmi Aulia Rizqi; Noor Idha Handajani; Yudith Dian Prawitri; Lydia Arfianti; Abdul Jabbar Al Hayyan; Atika Atika (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Osteoarthritis (OA) is an age-related degenerative disease affecting the subchondral tissue of articular and bone cartilage, leading to biomechanical changes that cause pain, stiffness, and balance impairment, which increases fall risk and its severe consequences, including fractures, joint dislocations, loss of independence, and even death. Dynamic balance function can be assessed using the four square step test (FSST), a recommended functional test for knee OA patients. Knee OA management continues to develop, introducing regenerative therapies such as dextrose prolotherapy and extracorporeal shock wave therapy (ESWT). Therefore, this study aims to analyze the effects of dextrose prolotherapy and ESWT on dynamic balance outcomes. Methods: Twenty-one subjects with unilateral knee osteoarthritis (grade II-III) were randomly assigned to either the dextrose prolotherapy or ESWT therapy group. The dextrose prolotherapy group received three injections, with a 3-week interval between each. The ESWT group underwent six sessions of therapy spaced one week apart. FSST was assessed before and after the intervention. Results: Significant improvements in dynamic balance function, as measured by the FSST (p < 0.05), were observed within each group when comparing pre-and post-intervention results. However, no significant difference (p > 0.05) was found in FSST outcomes between the two groups. No severe adverse effects were reported in patients from either group. Conclusion: This study demonstrates a positive impact of dextrose prolotherapy and ESWT therapy on the dynamic balance function of patients with knee OA. Both interventions were equally effective in improving dynamic balance function.